0.6(6+7x)-2x=0.4(4+3x)+3

Simple and best practice solution for 0.6(6+7x)-2x=0.4(4+3x)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.6(6+7x)-2x=0.4(4+3x)+3 equation:


Simplifying
0.6(6 + 7x) + -2x = 0.4(4 + 3x) + 3
(6 * 0.6 + 7x * 0.6) + -2x = 0.4(4 + 3x) + 3
(3.6 + 4.2x) + -2x = 0.4(4 + 3x) + 3

Combine like terms: 4.2x + -2x = 2.2x
3.6 + 2.2x = 0.4(4 + 3x) + 3
3.6 + 2.2x = (4 * 0.4 + 3x * 0.4) + 3
3.6 + 2.2x = (1.6 + 1.2x) + 3

Reorder the terms:
3.6 + 2.2x = 1.6 + 3 + 1.2x

Combine like terms: 1.6 + 3 = 4.6
3.6 + 2.2x = 4.6 + 1.2x

Solving
3.6 + 2.2x = 4.6 + 1.2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1.2x' to each side of the equation.
3.6 + 2.2x + -1.2x = 4.6 + 1.2x + -1.2x

Combine like terms: 2.2x + -1.2x = 1x
3.6 + 1x = 4.6 + 1.2x + -1.2x

Combine like terms: 1.2x + -1.2x = 0.0
3.6 + 1x = 4.6 + 0.0
3.6 + 1x = 4.6

Add '-3.6' to each side of the equation.
3.6 + -3.6 + 1x = 4.6 + -3.6

Combine like terms: 3.6 + -3.6 = 0.0
0.0 + 1x = 4.6 + -3.6
1x = 4.6 + -3.6

Combine like terms: 4.6 + -3.6 = 1
1x = 1

Divide each side by '1'.
x = 1

Simplifying
x = 1

See similar equations:

| 2(2n-5)=4 | | 13x+7y=42 | | 0=x^2+8x+11 | | 9y^2+18y+2=0 | | 3+5.2=1-2.8x | | 4x-4x-28=-28 | | X+6+7x=14 | | n/7=33/21 | | -4d-2(3+d)=14 | | -38+49= | | 2-7x=-61 | | 3x^2+14w+8=0 | | 9x^2+6xy+y^2= | | 1.52+2= | | -42+(-55)= | | 2x+3y=135 | | -z+4(x+3)=-12 | | X^2-12x=-x | | 11x-x=14 | | 4b^5+8b+7=4 | | (5x/2)-(5x/6) | | 3s-5t=7t | | -6+9=21 | | 84=4n | | 2x+3.75=7x | | 2x^3-15X^2=2x | | 2x-b+8=5b+4 | | h(x)=2x+4 | | 2532500/x/1277.59=27.68 | | z+2(4+z)=3z+8 | | (3x^4y^3)(9x^2y^6)= | | 10y=2x+5 |

Equations solver categories